Energetic modeling, simulation and experimental of hydrogen desorption in a hydride tank. (8th January 2019) - Chabane, D.; Harel, F.; Djerdir, A.; Candusso, D.; Elkedim, O.; Fenineche, N.
Abstract: This paper presents a zero-dimensional (0D) model of hydride tank. The model aims to study the dynamic heat and mass transfers during desorption process in order to investigate the thermal-fluidic behaviors of this hydride tank. This proposed model has been validated experimentally thanks to a tailor-made developed test bench. This test bench allows the hydride characterization at tank scale and also the energetic characterization. The simulation results of the heat exchanges and mass transfer in and between the coupled reaction bed, show good agreement with the experimental ones. It is shown that the heat produced by a Proton Exchange Membrane Fuel Cell (PEMFC) (estimated starting from an electrical model) is enough to heat the metal alloy (FeTi) and therefore release the hydrogen with a sufficient mass flow rate to supply the PEMFC. Furthermore, the obtained results highlight the importance of the developed model for energy management of the coupling of fuel cell and hydride tank system. Highlights: A hydrogen storage. Energetic modeling of the hydride tank. Presentation of the two characterization process PCT and energetic during hydrogen desorption. Experimental validation.